Review Artikel: Aktivitas Farmakologis dari Metabolit Sekunder Tanaman Rambai (Baccaurea motleyana) - Ira Qadariah (Aesculapius Medical Journal, 2026)
Abstract [Review Article: Pharmacological Activity of the Secondary Metabolites of the Rambai (Baccaurea motleyana) Plant] Rambai (Baccaurea motleyana) is used empirically in Indonesia and has been investigated as a source of secondary metabolites. However, evidence on the plant parts studied, extraction methods, solvents, metabolite profiles, and pharmacological activities remains scattered. This narrative review synthesized primary studies published in 2020–2025. Google Scholar was searched using the core phrase “Baccaurea motleyana” combined with phytochemical/fitokimia, secondary metabolite/metabolit sekunder, pharmacological activity/aktivitas farmakologis, and bioactivity/bioaktivitas. Eligible articles comprised laboratory experimental studies conducted in vitro and/or in vivo and phytochemical analyses. Sixteen articles met the inclusion criteria. Leaves were the most frequently investigated plant part (9/16; 56.25%), and maceration was the predominant extraction method (14/16; 87.5%). Methanol was reported as a solvent in 8 of 16 articles (50%); individual articles could report more than one solvent. Reported metabolites included flavonoids, steroids, phenolics, saponins, terpenoids, alkaloids, tannins, eugenol, 4-ethyl-2-methoxy-phenol, beta-carotene, and ascorbic acid. Reported activities included antibacterial, antioxidant, antidiabetic, antipyretic, analgesic, antianemic, antidiarrheal, and antidepressant effects. Antiproliferative activity was demonstrated only in vitro in PANC-1 cells, whereas anticancer potential in several studies was primarily inferred from BSLT/BSLA toxicity assays or chemical-component identification and therefore does not establish anticancer efficacy in humans. The evidence remains predominantly preclinical. Standardized extracts, isolation and characterization of active compounds, robust toxicity testing, and further in vivo and clinical studies are required to establish efficacy and safety. Keywords: Baccaurea motleyana, pharmacological activity, phytochemicals, rambai, secondary metabolites